2019
DOI: 10.1371/journal.pone.0212879
|View full text |Cite
|
Sign up to set email alerts
|

The effect of refining process on the physicochemical properties and micronutrients of rapeseed oils

Abstract: Information on the physicochemical variability in rapeseed oil from different varieties during each refining process is lacking. Our purpose was to investigate the physicochemical properties, micronutrients and oxidative stability of the oil extracted from the five varieties of rapeseeds during their different stages of refining process. Increase in the acid value, peroxide value and p -anisidine value were detected in the refining, while content of tocopherols, sterols, β-carotene and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 35 publications
(40 reference statements)
9
66
2
1
Order By: Relevance
“…The neutralization step led to an elimination of 11.3% of the remaining total phytosterols. Wu (2019) observed that the reduction of phytosterols was a result of micelle formation (of free sterols and soap) during neutralization. In addition, the losses in the degumming and bleaching steps were 6.6% and 1.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neutralization step led to an elimination of 11.3% of the remaining total phytosterols. Wu (2019) observed that the reduction of phytosterols was a result of micelle formation (of free sterols and soap) during neutralization. In addition, the losses in the degumming and bleaching steps were 6.6% and 1.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The method used to analyze the content of phytosterols was based on the previous procedure with slight modifications (Wu et al., 2019). Accurately, 100 µg of 5α‐cholestane was diluted as an internal standard to a 2 mg/mL solution in chloroform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned for phenolic compounds, for tocopherol only a few studies have evaluated the impact of the refining process on its content in olive oil samples, while most published articles are focused on other types of vegetable oils [30][31][32]. In general, a continuous decrease of tocopherol content has been observed during the refining procedure in sunflower, rapeseed, and soybean oils [6,33].…”
Section: Samplesmentioning
confidence: 99%
“…Rapeseed oil is a major source of vegetable oil in the world. Its production is estimated at 27.71 million metric tons, the third just behind palm and soybean oil, supporting the 2018 official data of the United States Department of Agriculture [12]. It contains around 1.5-6% palmitic acid, around 0.5-3.1% stearic acid, around 28% oleic acid, around 11-23% linoleic acid, and around 5-13% linolenic acid [13].…”
Section: Introductionmentioning
confidence: 52%